Performance analysis of the tactical systems of a professional soccer - Moises Falces Prieto; Isaac Marcos Gutiérrez; Alberto Martín Barrero (Federación Extremeña de Balonmano; University of Extremadura, 2021)
In this study we try to observe, code and analyze the performance that different tactical systems offer to a professional soccer team. Through the observational method and the use of the SWOT analysis tool, the use of the game systems of the matches carried out before the covid19 (n = 25) of the 19-20 season is analyzed. Performance-related variables were analyzed taking into account the gaming system used and its context, in addition to performing a SWOT that would allow obtaining data on strategic factors of each system. The game systems were (1-4-2-2-2; 1-3-1-4-2; 1-3-4-3; 1-3-4-1-2; 1-4-2- 3-1). The 1-4-2-2 system was the most used (52%), it achieved more victories (57.14%), more draws (50%), most used as a visitor (46.15%) and at home (58.33%). The 3-defense game system prevailed when the rival used a striker (54.55%) and at the offensive level a system with two forwards was used 83% of times against a defense of 3. We can conclude that the analyzed team obtained a high performance After using a wide variety of game systems, obtaining advantages in competition that the SWOT tool helps us to collect in a simple, economical and efficient way.